ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING PERIODE 2019-2021 - Hanifa, Hilmiyatul; Wahyuni, Ika; Sari, Lita Permata (Fakultas Ekonomi dan Bisnis, 2023)
The aim of this research is to analyze the factors that influence company value in food and beverage companies listed on the Indonesian Stock Exchange with profitability as an intervening variable for the 2019-2021 periods. The population in this study was all 30 food and beverage companies registered on the IDX. The sampling technique in the research used purposive sampling so that 10 data analysis samples were obtained. Data analysis and hypothesis testing in this study used the Smart PLS 3.0 application. The results of this study indicate that capital structure has a positive but not significant effect on profitability. While Liquidity has a negative but not significant effect on profitability. Capital structure and liquidity have no significant effect on firm value. Profitability has a significant positive effect on firm value. Capital structure and liquidity have no significant effect on company value through profitability.